Proceedings of the 2020 DigitalFUTURES : The 2nd International Conference on Computational Design and Robotic Fabrication (CDRF 2020) - Yuan, Philip F.; Yao, Jiawei; Yan, Chao; Wang, Xiang; Leach, Neil; Yuan, Philip F.; Yao, Jiawei; Yan, Chao; Wang, Xiang; Leach, Neil (Springer Nature, 2021)
This open access book is a compilation of selected papers from 2020 DigitalFUTURES$1 (BThe 2nd International Conference on Computational Design and Robotic Fabrication (CDRF 2020). The book focuses on novel techniques for computational design and robotic fabrication. The contents make valuable contributions to academic researchers, designers, and engineers in the industry. As well, readers will encounter new ideas about understanding intelligence in architecture.s
English
Keywords: Robotics; Computer-aided design (CAD); Computer modelling & simulation; Artificial intelligence; Robotics and Automation; Computer-Aided Engineering (CAD, CAE) and Design; Simulation and Modeling; Robotics; Control, Robotics, Automation; Computer Science; Post-humanist Intelligence; Computational Design; Robotic Fabrication; Human-Machine Collaboration; AI in Architecture; Open Access; Computer-aided design (CAD); Computer modelling & simulation; Artificial intelligence